IMAGE ANALYSIS OF CHROMATIN IN CELLS OF PREIMPLANTATION MOUSE EMBRYOS - Sawicki, Wojciech (The Rockefeller University Press, 1974)
Mouse two-celled embryos and blastulae were Feulgen stained and the DNA content of their nuclei was measured with an integrating microdensitometer. The cells considered on the basis of their nuclear DNA content to be in G(1), S, and G(2) phases of the cell cycle were selected and their total chromatin area and chromatin areas at different gray levels were measured by the image analyzing computer, Quantimet. The measurements were aimed at quantitation of several features of the chromatin morphology of cells in different functional states. The total area of chromatin was found to increase, and the mean density of chromatin to decrease, from the G(1) to the G(2) phase of the cell cycle in both two-celled embryos and blastulae. The area of chromatin decreased, and the mean density of chromatin increased, as embryos developed from two-celled to blastula stage. It was concluded that nuclear morphology in preimplantation mouse embryos depends on both the phase of the cell cycle and the stage of development. The method of image analysis described was found to be useful for quantitation of changes in chromatin morphology.